Pengaruh Substitusi Tepung Kacang Hijau (Vigna Radiata ) Terhadap Nilai Gizi (Serat Dan Karbohidrat) Dan Daya Terima Cookies Tepung Ubi Jalar Ungu (Ipomoea Batatas L) - Erlinawati, Indira; Wijaningsih, Wiwik (JURNAL RISET GIZI, 2014)
Background : Food diversification program aims to improve the food consumption and to reduce reliance on one types of food, especially rice. The program is carried out by considering local produce available and less utilization. One examples of product is purple sweet potato flour cookies.Aims : This study is to determine the effect of green bean flour substitution on nutritional value (fiber and carbohydrates) as well acceptance of purple potato cookies with green bean flour substitution of )%, 10%, 20% and 30%.Method : Design that is used by this study is a random design completely with two repetitions that are measurement of levels of fiber and carbohydrate done in duplicate. The level of acceptance measurement test performed by 25 trained panelists who know about the organoleptic testing.Result : The resultÂ  showed, sweet potato flour cookies with green bean flour substitution as much as 30% has the highest fiber content of 0,22g% and the highest carbohydrates content of 63,28%. Based on the results of statistical test ANOVA, green bean fluor substitution of sweet potato cookies has significant effect for fiber and carbohydrates, with p-value 0,00. Acceptance of test results showed the influence of green bean fluor substitution for acceptance of cookies purple sweet potato fluor. Purple sweet potato cookies with green bean fluor substitution of 20% are the most favored cookies with an average score of 3,95.Conclusion : The result above it can be concluded that there is a substitution effect of green bean fluor on the nutritional value (fiber and carbohydrates) and acceptance of cookies.